Microplastics in oysters (Crassostrea gigas) and water at the Bahía Blanca Estuary (Southwestern Atlantic): An emerging issue of global concern - Fernandez Severini, Melisa Daiana; Villagran, Diana Mariel; Buzzi, Natalia Sol; Sartor, G. Chatelain (Regional Studies in Marine Science)
Detection of microplastics (MPs) in biotic and abiotic matrices is relevant to evaluate how marine ecosystem's exposure to these pollutants is of emerging environmental concern and at risk of loss of functionality and biodiversity. The presence of MPs was studied for the first time in the gut of benthic oysters (Crassostrea gigas) and in the water column in a eutrophic estuary under high anthropogenic pressure, in the southwestern Atlantic. Significant abundances of small plastic debris were found at all the sampling stations- mainly fibers, fragments, pellets, and beads. MPs were categorized and counted according to type, color, and size. Microfibers presented the highest percentage of abundance in the water column (98% with Van Dorn bottles and 72.73 % with a 60μm plankton net) as well as in oysters (91%). In water collected with Van Dorn bottles, the total MP concentrations ranged from 5900 to 782,000 particles/m3 and from 42.6 to 113.6 particles/m3 in samples collected with a 60μm plankton net. The widespread presence of fibers in all the assessed components could be related to the intense harbor activities in the area, such as the use of ropes for the mooring of boats and from fishing nets, as well as from domestic and industrial effluents. The presence of MPs in both the pelagic and benthic realms may imply risk for the animals that inhabit the estuary, and for human wellbeing, with respect to the potential transfer of MPs through the food web, affecting the provisioning of ecosystem services. Fil: Fernandez Severini, Melisa Daiana. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Bahía Blanca. Instituto Argentino de Oceanografía. Universidad Nacional del Sur. Instituto Argentino de Oceanografía; Argentina Fil: Villagran, Diana Mariel. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Bahía Blanca. Instituto Argentino de Oceanografía. Universidad Nacional del Sur. Instituto Argentino de Oceanografía; ...